2006
DOI: 10.1159/000098208
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bleomycin-Induced Skin Fibrosis in Mice Lacking the Th1-Specific Transcription Factor T-bet

Abstract: Fibrosis, the pathological hallmark of scleroderma and related conditions, is due to sustained activation of tissue fibroblasts. Accumulating evidence implicates cytokine networks in initiating, and propagating or terminating fibroblast activation, and the specific cytokine phenotype dictates evolution of the fibrotic response toward either resolution or scarring. In particular, cytokines that promote fibroblast proliferation and myofibroblast differentiation and extracellular matrix (ECM) accumulation functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 76 publications
(41 reference statements)
1
37
1
Order By: Relevance
“…Animal studies provide support for the role of a polarized immune response in the pathogenesis of fibrosis. For example, Th2-polarized cells can induce fibrosis when passively transferred in vivo (41), and mice lacking the Th1-specific transcription factor T-bet show exaggerated skin fibrosis in response to bleomycin (42). Patients with SSc display a relative shift in the Th1-Th2 cytokine balance toward Th2 predominance.…”
Section: Pathogenesis: An Integrated View Of Vascular Damage and Automentioning
confidence: 99%
“…Animal studies provide support for the role of a polarized immune response in the pathogenesis of fibrosis. For example, Th2-polarized cells can induce fibrosis when passively transferred in vivo (41), and mice lacking the Th1-specific transcription factor T-bet show exaggerated skin fibrosis in response to bleomycin (42). Patients with SSc display a relative shift in the Th1-Th2 cytokine balance toward Th2 predominance.…”
Section: Pathogenesis: An Integrated View Of Vascular Damage and Automentioning
confidence: 99%
“…Animal studies provide support for the role of a polarized immune response in the pathogenesis of fibrosis. Transcriptome analysis in animal models of inflammation has shown that genes involved in wound healing and fibrosis are associated with Th2 polarized responses [30,31], and IL-13 was shown to have an important role in the mouse model of bleomycin-induced fibrosis [32,33].…”
Section: T Cell Polarized Responsesmentioning
confidence: 99%
“…Type 2 polarized T cells secrete large amounts of IL-4, IL-5, and IL-13 and low levels of type 1 cytokines, such as interferon-␥ (IFN␥) (18). Findings in animal studies provide support for the role of a polarized immune response in the pathogenesis of fibrosis (19,20). Although reports concerning the balance of type 1 and type 2 cytokines in SSc patients are conflicting, most studies suggest that the immunopathologic response is dominated by type 2 cytokines (21-30).…”
mentioning
confidence: 97%